Effect of monovalency on anti-contactin-1 IgG4 - Taieb, Guillaume; Jentzer, Alexandre; Vegezzi, Elisa; Lleixà, Cinta; Illa, Isabel; Querol, Luis; Devaux, Jérôme J. (Frontiers in Immunology, 2023)
Introduction Autoimmune nodopathies (AN) have been diagnosed in a subset of patients fulfilling criteria for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) who display no or poor response to intravenous immunoglobulins. Biomarkers of AN are autoantibodies, mainly IgG4, directed against the ternary paranodal complex composed by neurofascin-155, contactin-1 (CNTN1), and Contactin-associated-protein-1 (CASPR1) or against the nodal isoforms of neurofascin. IgG4 can undergo a Fab-arm exchange (FAE) which results in functionally monovalent antibody. This phenomenon differentially affects the pathogenicity of IgG4 depending on the target of autoantibodies. Here, we have evaluated this issue by examining the impact of valency on anti-CNTN1 IgG4 which induces paranodal destruction through a function blocking activity. Methods Sera were obtained from 20 patients with AN associated with anti-CNTN1 antibodies. The proportion of monospecific/bispecific anti-CNTN1 antibodies was estimated in each patient by ELISA by examining the ability of serum antibodies to cross-link untagged CNTN1 with biotinylated CNTN1. To determine the impact of monovalency, anti-CNTN1 IgG4 were enzymatically digested into monovalent Fab and tested in vitro on cell aggregation assay. Also, intraneural injections were performed to determine whether monovalent Fab and native IgG4 may penetrate paranode, and antibody infiltration was monitored 1- and 3-days post injection. Results and discussion We found that the percentage of monospecific antibodies were lower than 5% in 14 out of 20 patients (70%), suggesting that IgG4 have undergone extensive FAE in situ. The levels of monospecific antibodies correlated with the titers of anti-CNTN1 antibodies. However, no correlation was found with clinical severity, and patients with low or high percentage of monospecific antibodies similarly showed a severe phenotype. Native anti-CNTN1 IgG4 were shown to inhibit the interaction between cells expressing CNTN1/CASPR1 and cells expressing neurofascin-155 using an in vitro aggregation assay. Similarly, monovalent Fab significantly inhibited the interaction between CNTN1/CASPR1 and neurofascin-155. Intraneural injections of Fab and native anti-CNTN1 IgG4 indicated that both mono- and bivalent anti-CNTN1 IgG4 potently penetrated the paranodal regions and completely invaded this region by day 3. Altogether, these data indicate anti-CNTN1 IgG4 are mostly bispecific in patients, and that functionally monovalent anti-CNTN1 antibodies have the pathogenic potency to alter paranode.